2010
DOI: 10.1007/s10661-010-1640-z
|View full text |Cite
|
Sign up to set email alerts
|

Imposex and butyltin concentrations in Bolinus brandaris (Gastropoda: Muricidae) from the northern Tunisian coast

Abstract: The imposex incidence and butyltin concentration i.e. tributyltin with its di- and mono-substituted metabolites were investigated in the muricid Bolinus brandaris sampled from two sites on the northern Tunisian coast (the Lagoon of Bizerta and the small Gulf of Tunis). Both populations had imposex, with stages of imposex development varying between VDS 1 and VDS 4.3. All imposex indices (imposex frequency (I %), female penis length, female vas deferens length, vas deferens sequence index, relative penis length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
(50 reference statements)
2
9
0
Order By: Relevance
“…Sexual identification was based on the presence or absence of the vagina and capsule gland. After opening the mantle cavity, imposex analysis (including the measurement of penis length -PL) was performed as described by Abidli et al (2009aAbidli et al ( , 2011. Macroscopic examination of the gonads in both sexes and of the capsule gland in females was Growth and reproduction of Bolinus brandaris.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sexual identification was based on the presence or absence of the vagina and capsule gland. After opening the mantle cavity, imposex analysis (including the measurement of penis length -PL) was performed as described by Abidli et al (2009aAbidli et al ( , 2011. Macroscopic examination of the gonads in both sexes and of the capsule gland in females was Growth and reproduction of Bolinus brandaris.…”
Section: Methodsmentioning
confidence: 99%
“…Like approximately 200 gonochoristic neogastropod species (Shi et al 2005;Sternberg et al 2010), B. brandaris is affected by imposex throughout its distributional range Solé et al 1998;Ramón & Amor 2001;Chiavarini et al 2003;Lemghich & Benajiba 2007;Vasconcelos et al 2010Vasconcelos et al , 2011Abidli et al 2009aAbidli et al , 2011Abidli et al , 2012. In B. brandaris sampled from two sites along the northern Tunisian coast (Bizerta Lagoon and small Gulf of Tunis), the stages of imposex development varied between VDS 1 and VDS 4.3, with all imposex indices being significantly higher in snails from the Bizerta lagoon (Abidli et al 2011). Imposex frequency was also higher in gastropods collected from the Lagoon of Bizerta than from the small Gulf of Tunis (93.9% against 65.7%), corroborating TBT analysis in the whole tissues of female B. brandaris from the two collecting sites (Abidli et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, this lagoon has been subjected to many anthropogenic pressures including urbanization, agricultural activities (pesticides and chemical fertilizers), industrial activities (cement works, metallurgical industry, boatyards), and naval and commercial shipping activities. The direct and indirect discharges of urban, agricultural and industrial wastes and runoff have resulted in the increase of chemical contamination of the lagoon by various toxic compounds such as polychlorinated biphenyls (PCBs) (Derouiche et al, 2004;Ben Ameur et al, 2013;Barhoumi et al, 2014a), organochlorine pesticides (OCPs) (Ben Ameur et al, 2013;Barhoumi et al, 2014a), polycyclic aromatic hydrocarbons (PAHs) (Trabelsi and Driss, 2005;Barhoumi et al, 2014b), polybrominated diphenyl ethers (PBDEs) and their methoxylated analogues (MeO-PBDEs) (Ben Ameur et al, 2011, organotins (Abidli et al, 2011) and heavy metals (Ben Garali et al, 2010). This has led to a decrease in bivalve and fish production over the last few decades (ANPE, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In Tunisian waters, B. brandaris is found in the Bizerte lagoon and in the Gulf of Tunis (northern Tunisia) (e.g. Abidli et al, 2009Abidli et al, , 2011, constitutes an important component of the benthic communities in the Gulf of Gabès (southern Tunisia), and is one of the most common shellfish species caught as by-catch by bottom trawlers. Recent fishing surveys in this area (dealing with stock assessment and population structure of the fishing resources) showed that B. brandaris is mainly found in the 10−80 m depth range, with 45 and 60 m depth providing the highest catches per unit effort (CPUE = total biomass / hour) (K. Elhasni, unpublished data).…”
Section: Introductionmentioning
confidence: 99%